An extensive analysis and examination of techniques to enhance the efficiency of water extraction from wastewater generated during the recycling of nickel manganese cobalt (NMC) batteries using reverse osmosis membrane technology. - Prasetya, Agus; Mulyono, Panut; Sujoto, Vincent Sutresno Hadi; Warmita, Helena Karunia; Perdana, Indra; Sutijan, Sutijan; Astuti, Widi; Sumardi, Slamet; Jenie, Siti Nurul Aisyiyah (Jurnal Rekayasa Proses, 2024)
Industrial water consumption will account for 22% of global water demand by 2030. Industry water conservation is encouraged by rapid corporate growth. Industrial resource usage and pollutant emissions can be reduced via cleaner production methods. Recycling is essential to greener production and the circular economy. Recycling is crucial to achieving the 2030 Sustainable Development Goals. The electric vehicle (EV) sector has propelled battery business growth in recent years, especially in Indonesia. The electric vehicle (EV) sector will benefit from using Nickel Manganese Cobalt (NMC) batteries. The study will use reverse osmosis (RO) membrane filtration to recover water from recovered NMC battery effluent. The experiment will investigate feed solution concentrations, pressures (8, 10, and 12 bar), and temperatures (30, 40, and 50°C). Two factors—permeate flux and metal ion rejection—determine reverse osmosis membrane efficiency. Li and Na metal rejection was maximum at 30°C and 12 bar, with 94-96% and 90-93% rejection rates, respectively. Under certain operating conditions, reverse osmosis membrane technology significantly reduced sodium (Na) concentration in NMC battery recycling effluent. Thus, wastewater is no longer saline. Reverse osmosis water can be reused for cooling due to its Li and Na concentrations.